Vedic Sacrifice and the Pentadic Theory of Indo-European Ideology. (19th December 2015) - Allen, Nick
Abstract : If the Sanskrit language derives from the unattested but reconstructable proto-Indo-European language, ideas expressed in Sanskrit might derive from a reconstructable proto-Indo-European ideology. In fact, a body of comparative work on material from various regions of the ancient Indo-European-speaking world suggests that such a proto-ideology once existed, and that it survived long enough to leave significant traces in the historical sources. Traces of a pentadic ideology, one based on five 'supercategories', have been recognized in many areas of Sanskritic culture, including the varṇa schema, Sāṃkhya and Yoga philosophies, and the plot, heroes and gods of the Mahābhārata. The present article extends the search for pentadic patterns into Vedic ritual (referring mainly to the Śatapatha Brāhmaṇa). In doing so it explores the agents (both human and non-human) that participate in a sacrifice, the classification of offerings, and the layout of the sacrificial ground (both the smaller standard one and the larger uttaravedi). The aim is at the same time to contribute to understandings of the history of the Hindu tradition and to strengthen the hypothesis of an Indo-European pentadic ideology.